Kepemilikan Satuan Rumah Susun Bagi Warga Negara Asing Di Indonesia - Heni Nikita Ransa; Siti Malikhatun Badriyah (Notarius, 2023)
AbstractForeigners domiciled in Indonesia need a residential house or a residence in the form of an apartment unit. Foreigners may own flats in Indonesia but with certain limitations in which the regulations regarding ownership of flats for foreigners have been updated. The purpose of this research is to find out how the ownership of condominium units is arranged and how the ownership restrictions are for foreigners in Indonesia. The results obtained are that the first owner of flats for foreigners in Indonesia is now regulated in the Job Creation Law, PP No. 18 of 2021, and Permen ATR/Head of BPN No. 29 of 2016. Both foreigners have flats in Indonesia which are limited to flats built-in on plots of land with Right of Use or Right of Building on state land, Right of Use or Right of Building on land Right of Management and Right of Use or Right of Building on land with Hak Milik and foreigners who have immigration documents such as visas, passports or residence permits issued by the competent authority.Keywords: foreign citizens; flats; ownershipAbstrakWNA yang berkedudukan di Indonesia membutuhkan rumah hunian atau rumah tinggal berupa satuan rumah susun. WNA boleh memiliki rumah susun di Indonesia tetapi dengan batasan-batasan tertentu yang mana pengaturan mengenai kepemilikan rumah susun bagi WNA sudah diperbaharui. Tujuan penelitian untuk mengetahui bagaimana pengaturan pemilikan sarusun dan bagaimana pembatasan kepemilikannya bagi WNA di Indonesia. Hasil yang diperoleh adalah pertama kepemilikan satuan rumah susun bagi WNA di Indonesia sekarang diatur dalam Undang-Undang Cipta Kerja, PP No 18 Tahun 2021 dan Permen ATR/Kepala BPN No 29 Tahun 2016. Kedua WNA memiliki satuan rumah susun di Indonesia sebatas rumah susun yang dibangun di atas bidang tanah Hak pakai atau Hak Guna Bangunan di atas tanah negara, Hak pakai atau Hak Guna Bangunan di atas tanah Hak Pengelolaan dan Hak pakai atau Hak Guna Bangunan di atas tanah Hak Milik dan WNA yang mempunyai dokumen keimigrasian seperti visa, paspor atau izin tinggal yang dikeluarkan oleh instansi yang berwenang.Kata kunci: WNA; sarusun; kepemilikan